Genetic mapping of a susceptibility locus for disc herniation and spastic paraplegia on 6q23.3-q24.1. Issue 6 (1st June 2002) - Zortea, M; Vettori, A; Trevisan, C P; Bellini, S; Vazza, G; Armani, M; Simonati, A; Mostacciuolo, M L
Abstract : It has been suggested that a genetic factor(s) or a familial predisposition may contribute to the clinical manifestations of disc herniation; moreover, no genetic linkage between spinal disc herniation and spastic paraplegia has ever been described. A family with consanguineous parents and four of eight sibs affected by multiple disc herniations and spastic paraplegia was clinically and genetically analysed. Surgery caused partial improvement in all of them. After the exclusion of type II collagen and vitamin D receptor genes and the recessive loci for HSPs, a genome wide search was performed with about 500 fluorescent markers. Positive lod score values were obtained for chromosome 6q22.31-q24.1, with evidence of three homozygous intervals. The maximum multipoint lod score of 3.28 was obtained in only one interval, between markers D6S1699 and D6S314. On the whole, a susceptibility locus for disc herniation and autosomal recessive spastic paraplegia was found on chromosome 6q23.3-q24.1. This is the first time that disc herniation and the associated neurological syndrome has been linked to a human chromosomal region.